Hiligaynon Lessons - Motus, Cecile L. (University of Hawai'i Press, 2023)
The Philippines series of the PALI Language Texts, under the general editorship of Howard P. McKaughan, consists of lesson textbooks, grammars, and dictionaries for seven major Filipino languages.